Análisis de los factores de competitividad para la productividad sostenible de las PYMES en Trujillo (Perú); Analysis of competitiveness factors for the sustainable productivity of SMEs in Trujillo (Peru) - Luis Alberto Benites Gutierrez; Claudio Ruff Escobar; Marcelo Ruiz Toledo; Alexis Matheu Pérez; Martín Inca Alayo; Paola Juica Martínez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2020)
– The levels of competitiveness of the countries of Latin America are in a process of slow development to reach those companies located in more modern economies, because they have difficulties in some fundamental pillars of competitiveness such as the levels of technological innovation based on intelligent infrastructure investments, intellectual capital, that have a major impact on multifactor productivity. The objective of this research was to analyze the competitive situation of Small and Medium Enterprises (SMEs) in the city of Trujillo, evaluating the key factors for productivity that will have an association with sustainable competitiveness. For this, the first step was to develop review of the fundamental literature for the hypotheses and the empirical study applied to 152 entrepreneurs in various sectors of the city of Trujillo, compiling the opinion of qualitative and quantitative type and statistical processing. The results obtained were that 70% of the companies in the footwear sector are prepared to respond to the five competitive forces of Porter, for the mechanical metal sector 89% of the companies, 70% of the textile companies are competitive. Through linear regressions, we identify that quality, human capital, finance, strategic plan, marketing and strategic alliances have a positive relationship with competitiveness, however when integrated with ICTs, the synergy of the business is not appreciated. The findings are useful to improve knowledge in the strategic decisions of SME Managers to respond to Globalization and the intensive process of digitalization.
Keywords: C02; L67; M20; 330; key factors for productivity; sustainable competitiveness; strategic decisions